Use of Plasma Rich in Growth Factors and ReGeneraTing Agent Matrix for the Treatment of Corneal Diseases - Sánchez-Ávila, Ronald M. (Vision (Basel), 2021)
This study aimed to investigate the use of Plasma Rich in Growth Factors (PRGF) associated with tissue ReGeneraTing Agent (RGTA) drops for the treatment of noninfectious corneal ulcers. RGTA treatment was applied (one drop every two days); however, if ulcer closure was not achieved, PRGF eye drops treatment was added (four times/day). The time taken to reach the ulcer closure, the Best Corrected Visual Acuity (BCVA), intraocular pressure (IOP), Visual Analog Scale (VAS, in terms of frequency and severity of symptoms), and Ocular Surface Disease Index (OSDI) were evaluated. Seventy-four patients (79 eyes) were included, and the mean age was 56.8 ± 17.3 years. The neurotrophic corneal ulcer was the most frequent disorder (n = 27, 34.2%), mainly for herpes virus (n = 15, 19.0%). The time of PRGF eye drops treatment associated with the RGTA matrix was 4.2 ± 2.2 (1.5–9.0) months, and the follow-up period was 44.9 ± 31.5 months. The ulcer closure was achieved in 76 eyes (96.2%). BCVA, VAS and OSDI improved from the baseline (p < 0.001), and IOP remained unchanged (p = 0.665). RGTA and PRGF in noninfectious ulcers were effective and could be a therapeutic alternative for this type of corneal disease.